7+13s-2=9s+25-6s

Simple and best practice solution for 7+13s-2=9s+25-6s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+13s-2=9s+25-6s equation:


Simplifying
7 + 13s + -2 = 9s + 25 + -6s

Reorder the terms:
7 + -2 + 13s = 9s + 25 + -6s

Combine like terms: 7 + -2 = 5
5 + 13s = 9s + 25 + -6s

Reorder the terms:
5 + 13s = 25 + 9s + -6s

Combine like terms: 9s + -6s = 3s
5 + 13s = 25 + 3s

Solving
5 + 13s = 25 + 3s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3s' to each side of the equation.
5 + 13s + -3s = 25 + 3s + -3s

Combine like terms: 13s + -3s = 10s
5 + 10s = 25 + 3s + -3s

Combine like terms: 3s + -3s = 0
5 + 10s = 25 + 0
5 + 10s = 25

Add '-5' to each side of the equation.
5 + -5 + 10s = 25 + -5

Combine like terms: 5 + -5 = 0
0 + 10s = 25 + -5
10s = 25 + -5

Combine like terms: 25 + -5 = 20
10s = 20

Divide each side by '10'.
s = 2

Simplifying
s = 2

See similar equations:

| m-(4+2m)+3=2m+2 | | -6x+8=62 | | P^2+6=127 | | -107+k=-99 | | 12x+29=3x+254 | | x^4+2x^2=3x | | -16=y-25 | | 4y+11y=120 | | 102-6x=12x+20 | | [2x-3]=6 | | 28-k=-19 | | k-49=-62 | | 13-7x=88-42x | | (x)(6)=-30 | | 19-2x=5-10x | | -14t+7=49 | | -11.1x=77.7 | | 4x-f=-22 | | x-8.1=-3.7 | | -9(3b+2)+(28b-2)=0 | | -5-4+q=12 | | p^3+7p-6=0 | | 4s^2+8s=221 | | 5.3q-1.7-5.5q=-1.29-3.6 | | 2611x+622=126 | | 6y-15=y | | 23=3y+5 | | 223-5x=40x+18 | | 7y=3y+8 | | 11+x=5 | | 11.7=w+16.8 | | x-47=-46 |

Equations solver categories